Attitudes and behaviors of nursing professionals’ attitudes towards sexuality in old-age - Medina Fernández, Isaí Arturo; Torres Soto, Nissa Yaing; Medina Fernández, Josué Arturo; Torres Obregón, Reyna; Carrillo Cervantes, Ana Laura; Lizcano-Baños, Adrián Josué (Horizonte Sanitario, 2023)
Objective: to determine the intrapersonal factors that predict nursing professional attitudes towards sexuality in old age. Material and methods: Quantitative, observational, cross-sectional, and explanatory study, with a sample of 305 nursing professionals with a mean age of 29 years (SD=7.76), sexuality scales were applied, attitudes towards sexuality in old age and the questionnaire of attitudes to old age. The analysis was with descriptive and inferential statistics using SPSS. Results: It was found that attitudes towards sexuality, as well as towards old age, have a positive and significant impact on sexuality in old age in the nursing staff surveyed. Likewise, a statistically significant difference was found by sex for the dimensions of men regarding sexuality (p=.014) and sexual preoccupation (p=.000), as well as that of negative physical and behavioral stereotypes (p=.037) with higher scores for men (p<.05). Conclusion: intrapersonal factors such as age, sexual self-esteem and attitudes towards old age are predictors of attitudes towards sexuality in old age. Keywords: Attitude, Sexuality, Nursing Staff; Aging.